2005
DOI: 10.1016/j.jmb.2004.11.024
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Approach to Gain Insights into the Cellular Function of Human Ataxin-2

Abstract: Spinocerebellar ataxia type 2 (SCA2) is a hereditary neurodegenerative disorder caused by a trinucleotide expansion in the SCA2 gene, encoding a polyglutamine stretch in the gene product ataxin-2 (ATX2), whose cellular function is unknown. However, ATX2 interacts with A2BP1, a protein containing an RNA-recognition motif, and the existence of an interaction motif for the C-terminal domain of the poly(A)-binding protein (PABC) as well as an Lsm (Like Sm) domain in ATX2 suggest that ATX2 like its yeast homolog Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
151
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 88 publications
1
151
0
Order By: Relevance
“…Along this line, it has been reported that ATXN2 contains an Like Sm (LSm) domain that might be capable of RNA binding as observed for other LSm domain proteins (Neuwald and Koonin, 1998;Achsel et al, 2001;Albrecht et al, 2004). Further evidence for a likely role in RNA metabolism was provided by demonstrating that ATXN2 assembles with polysomes and interacts with the cytoplasmic poly(A)-binding protein 1 (PABP-C1) that functions in translation initiation and mRNA decay regulation (Ralser et al, 2005a;Satterfield and Pallanck, 2006). Proteomics-based results demonstrated that PABP and T-plastin, which itself associates with ATXN2, are present together in large protein complexes mostly consisting of proteins involved in RNA processing (Ho et al, 2002;Blagoev et al, 2003).…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Along this line, it has been reported that ATXN2 contains an Like Sm (LSm) domain that might be capable of RNA binding as observed for other LSm domain proteins (Neuwald and Koonin, 1998;Achsel et al, 2001;Albrecht et al, 2004). Further evidence for a likely role in RNA metabolism was provided by demonstrating that ATXN2 assembles with polysomes and interacts with the cytoplasmic poly(A)-binding protein 1 (PABP-C1) that functions in translation initiation and mRNA decay regulation (Ralser et al, 2005a;Satterfield and Pallanck, 2006). Proteomics-based results demonstrated that PABP and T-plastin, which itself associates with ATXN2, are present together in large protein complexes mostly consisting of proteins involved in RNA processing (Ho et al, 2002;Blagoev et al, 2003).…”
mentioning
confidence: 90%
“…Thus, ATXN2 seems to be required for the assembly of SGs. Furthermore, we included in the course of the abovedescribed experiments the PABP protein as an additional component of SGs that is of particular interest, because of its interaction with ATXN2 (Ralser et al, 2005a). Strikingly, we observed that the PABP immunoreactivity was dramatically increased in all cells with diminished ATXN2 level ( Figure 8A).…”
mentioning
confidence: 90%
See 3 more Smart Citations